STUDI LITERATUR : PENGGUNAAN APLIKASI KAHOOT DALAM EVALUASI HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA - Bunga Mawarni Merdu; Maqfirah Maqfirah; Ade Irfan (Jurnal Dedikasi Pendidikan, 2024)
The basis of this research is the problem of students' low math scores. This is caused by the lack of development in mathematics education, as a result students become less energetic, their learning motivation is small, and the inspiration they receive is low. In how to practice in learning, upgrading tools are one of the keys that really influence the success of the practice method. The many kinds of upgrading tools make the way to practice more varied. Research procedures using literary research. The strategy of dredging data from various sources of posts through searches on Google Scholar. From the results of a survey at the base of the post, the Kahoot could be an alternative. Kahoot can be an upgrading tool as well as games with the encouragement of an internet connection. Kahoot can also increase attention and support the digital generation training style. That way, teachers can make these notes as a reference for implementing innovations in training, especially in online learning.